Development of STEAM-Based Electronic Student Worksheets (E-LKPD) for Science Learning - Vivi Sebastiani Pandiangan; Abdul Hamid K.; Samsidar Tanjung (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2025)
Background: The use of student worksheets that are not yet STEAM-based likely contributes to low student achievement in science learning. Therefore, it is necessary to develop STEAM-based electronic student worksheets (E-LKPD) for science subjects.Aims: To develop STEAM-based E-LKPD that is feasible, practical, and effective to enhacing students’ science learning outcomes.Methods: This study utilized development research with the Borg & Gall development model. The instruments used in this research included learning needs observation sheets, validation sheets for media, material/content, and design, feedback sheets for teacher and student response, and learning outcome assessment sheets.Result: The research results show: (1) material validation scored an average of 98.06%, (2) media validation scored an average of 84.18%, (3) design validation scored an average of 97.11%, three of them categorized as very feasible. (4) individual trial scored 91.50% and small group trials 97.75%, categorized as very practical.  (5) field trial scored 97.75%, categorized as very practical. Furthermore, the experimental results using STEAM-based E-LKPD in the experimental class obtained an average learning outcome of 83, while the control class using LKPD published by Kemdikbud obtained learning outcomes of 78.5. Independent samples t-test result showed a significance value of t < 0.05 (0.024 < 0.05), therefore H0 was rejected and H1 was accepted. This means that the STEAM-based E-LKPD product developed is effective for improving student learning outcomes in science learning.Conclusion: The STEAM-based E-LKPD is very feasible, practical, and effective for improving science learning outcomes.